The Potential of Pomadasys argyreus (Popondok Fish) Oil as an Omega-3 Source from the Mangrove Ecosystems of Southeast Sulawesi - Nita Trinovitasari; Nurull Hikmah; Irnawati; Fadhillah, Nurul Aliah (Chempublish Journal, 2026)
One of the marine products with high nutritional value is the popondok fish (Pomadasys argyreus). This species is commonly found in the mangrove ecosystems of Sulawesi and is utilized as an easily accessible source of animal protein for coastal communities. This study aims to analyze the fatty acid composition and physicochemical characteristics of popondok fish oil (Pomadasys argyreus). The popondok fish samples were obtained from Lembo Village, North Konawe Regency, Southeast Sulawesi Province. The fish oil was extracted using the Soxhlet extraction method at 70°C with n-hexane as the solvent. The purified fish oil was then characterized for its physicochemical properties, including acid value, peroxide value, iodine value, and saponification value, and its fatty acid composition was analyzed using GC-FID. The measured acid and peroxide values of the popondok fish oil indicated good quality, while the iodine value met the national standard. The saponification value suggested that the fatty acids in the oil were predominantly medium- to long-chain. These findings were supported by the fatty acid composition analysis, which showed that 58.14% of the total fatty acids were unsaturated. It can be concluded that popondok fish oil has the potential to be utilized as a viable source of high-quality fish oil.